2007
DOI: 10.1038/sj.ejcn.1602736
|View full text |Cite
|
Sign up to set email alerts
|

Osmolality of preterm formulas supplemented with nonprotein energy supplements

Abstract: Background: Addition of energy supplements to preterm formulas is an optional strategy to increase the energy intake in infants requiring fluid restriction, in conditions like bronchopulmonary dysplasia. This strategy may lead to an undesirable increase in osmolality of feeds, the maximum recommended safe limit being 400 mOsm/kg. The aim of the study was to measure the changes in osmolality of several commercialized preterm formulas after addition of glucose polymers and medium-chain triglycerides. Methods: Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The effect on osmolality when supplementing infant formulas was found to be additive, suggesting that the final osmolality of a supplemented formula can be estimated when the osmotic effect of the respective additive(s) are known. It was evident that carbohydrate supplements caused the largest increase in osmolality, whereas fat supplements caused a minimal increase, which has also been demonstrated in previous studies (Agarwal et al ., ; Pereira‐da‐Silva et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on osmolality when supplementing infant formulas was found to be additive, suggesting that the final osmolality of a supplemented formula can be estimated when the osmotic effect of the respective additive(s) are known. It was evident that carbohydrate supplements caused the largest increase in osmolality, whereas fat supplements caused a minimal increase, which has also been demonstrated in previous studies (Agarwal et al ., ; Pereira‐da‐Silva et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Although manufacturers provide data on the osmolality of different infant formulas at a standard concentration, very little data exist for over‐concentrated or supplemented formulas. However, some studies have demonstrated an increase in osmolality when supplementing specialised infant formulas (Pereira‐da‐Silva et al ., ,b). This creates a dilemma in the dietitian's clinical practice, where the benefits of modifying formulas must be balanced against the unknown increase in osmolality and the potential contribution to NEC or osmotic diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…All formulas were prepared by the same investigator according to a previously reported methodology (Pereira‐da‐Silva et al. , 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In some BPD infants with worse pulmonary function requiring greater fluid restriction, some authors have proposed increasing the energy and macronutrient intake by adding modular supplements of protein, carbohydrate, and fat to enriched formulas [ 123 ]. This formula manipulation has the inherent risks of increasing the osmolality of feedings and compromising the energy/protein ratio [ 124 ].…”
Section: Nutritional Approach In the Prevention And Management Of Bpdmentioning
confidence: 99%